Mathematics Village: An Effective Educational Tourism for Increasing Children's Motivation and Changing Their Perspective of Mathematics - Novia Ariyanti; Nuril Lutvi Azizah; Fitri Nur Latifah (Universitas Muhammadiyah Sidoarjo, 2023)
Mathematics Village is an educational tourism destination for children in Dukuh Pakis Surabaya. This educational tour uses games with mathematical themes to increase children's motivation and change their perspective of mathematics. The activity was conducted in 4 posts, using observation, preparation, demonstration, and practice methods. The results showed that Mathematics Village was effective in increasing children's motivation and changing their perspective of mathematics. Children were more enthusiastic about learning mathematics through games and they were able to understand mathematical concepts more easily. This activity can be a model for other communities to develop mathematical educational tourism in their environment. Highlight: Mathematics Village is an educational tourism destination for children in Dukuh Pakis Surabaya. The activity uses games with mathematical themes to increase children's motivation and change their perspective of mathematics. The results showed that Mathematics Village was effective in increasing children's motivation and changing their perspective of mathematics. Keyword: Mathematics Village, Educational tourism, Children, Motivation, Mathematics